Improved One-Pot Synthesis of 1-Aryl-3-trifluoroacetyl-1H-pyrroles under Swern Oxidation - Zanatta, Nilo; Aquino, Estefania da C.; da Silva, Fabio M.; Bonacorso, Helio G.; Martins, Marcos A. P. (Synthesis, 2012)
This study describes an improved one-pot, four-step synthesis of a new series of 1-aryl-3-trifluoroacetyl pyrroles from the reaction of 3-trifluoroacetyl-4,5-dihydrofuran with arylamines, giving 1,1,1-trifluoro-3-(2-hydroxyethyl)-4-arylamino-3-buten-2-ones, which were directly submitted to Swern oxidation to furnish 1,1,1-trifluoro-3-(2-ethanal)-4-arylamino-3-buten-2-ones. Subsequent intramolecular cyclization of the corresponding enaminoaldehydes followed by aromatization rendered the title compounds in a 30 to 56% overall yield.
Keywords: trifloroacetyl groups; pyrroles; Swern oxidation; arylamines; trifluoromethyl